Analytical Study of Dynamic and Vibrational of Composite Shell with Piezoelectric Layer using GDQM Method - Moslemi Petrudi, Amin; Rahmani , Masoud; Scurtu, Ionut Cristian (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Piezoelectric materials, due to their electromechanical coupling properties, are widely used as actuators and sensors in intelligent structures to control vibrations and bends of multilayer sheets with piezoelectric layers. In this paper, the response of free vibrations of a multilayer composite shell with the new Generalized Differential Quadrature Method (GDQM) for different boundary conditions is investigated. The governing equations are obtained by assuming first-order shear theory and using Hamilton's principle. The generalized quadrature differential method is used to solve the obtained equations. To use this method, coding has been done in MATLAB software. Due to the same thickness of the layers, as the number of composite layers increases and the total thickness is constant, the thickness of each layer decreases, and consequently the thickness of the piezoelectric layer decreases. Comparing the results of this method with the work of other researchers shows that this method has good accuracy.